Cover Image. Issue 13 (12th August 2022) - Fang, Shengyu; Li, Lianwang; Weng, Shimeng; Zhang, Zhong; Fan, Xing; Jiang, Tao; Wang, Yinyan
Abstract : COVER ILLUSTRATION The supplementary motor area (SMA) syndrome is a surgery‐related complication that commonly occurs after removing SMA glioma and needs weeks to recover. Fang et al. investigated predisposing factors of network alterations for patients suffering from SMA syndrome with using preoperative resting‐state functional MR images. The lesion‐side upper limb‐related primary motor area and the cingulate cortex are found to be key nodes. The increasing nodal vulnerability and nodal efficiency of those regions cause patients to be susceptible to SMA syndrome and a delayed recovery. This image aims to reflect motor‐related functional networks alternations identified in surgery‐related SMA syndrome with using oriental culture elements.